Small cell cancer of the esophagus, treatment outcomes of a rare histological type - E. A. Toneev; A. A. Firstov; D. I. Nuretdinov; E. Yu. Savenko; E. P. Anokhina; A. A. Martynov; Yu. A. Karabanova (Сибирский онкологический журнал, 2024)
Purpose: To demonstrate treatment outcomes in two patients with small cell esophageal cancer. Cases reports. Patient M. was assigned to receive polychemotherapy (PC H) composed of etoposide 100 mg/ m2 intravenously on days 1–3 + cisplatin 80 mg/m2 on day 1, every 21 days for 6 cycles and lanreotide 120 mg subcutaneously, every 28 days, followed by chemoradiotherapy (CRT). The patient received 1 cycle of PCT , which was well tolerated. Then, the patient received a cycle of 3D-conformal radiation therapy concurrently with 2 cycles of chemotherapy: etoposide 120 mg/m2 + cisplatin 80 mg/m2. Chemoradiotherapy was well tolerated. Dysphagia regression to grade I was observed. Currently, the patient continues to receive treatment (etoposide 100 mg/ m2 intravenously on days 1–3 + cisplatin 80 mg/m2 on day 1, every 21 days for 6 cycles and lanreotide 120 mg subcutaneously, every 28 days) and tolerates it well. Patient A. was assigned to receive PCT with etoposide 120 mg/m2 + cisplatin 80 mg/m2. After 4 cycles of PCT , the follow-up CT images revealed disease progression (enlarged retroperitoneal lymph nodes). The patient underwent external bean radiation therapy to the primary tumor. Radiotherapy was relatively well tolerated. The patient underwent the course of radiation therapy relatively satisfactorily. Due to the progression of the disease, symptomatic treatment was assigned. The patient died 9 months after diagnosis. Conclusion. Small cell carcinoma of the esophagus is a rare histological type with poor prognosis. Concurrent platinum-based chemoradiotherapy allows achievement of stable disease and disease control.